EFL TEST ANXIETY AMONG CHINESE GRADUATE STUDENTS: EFFECTS OF TEST CHARACTERISTICS - Jie Xiaoping (Indonesian JELT, 2009)
The paper is a qualitative study of the effect of test characteristics on test anxiety among Chinese graduate students. Different from previous research, the study wants to emphasize the importance of test characteristics in controlling both trait and state test anxiety in EFL testing contexts. Research results suggest time pressure, item type, item difficulty sequencing and test taking information given would affect test takers’ trait and state test anxiety in EFL tests. Implications obtained from this study include EFL test designers should consider the effect of test characteristics on highly anxious test takers, and alter test methods to reduce the debilitating effects of test anxiety on test results so as to improve test validity and reliability. Keywords: Trait test anxiety, state test anxiety, test characteristics, EFL tests, Chinese graduate students.